Sensitive Biomarker Analysis of Xue-Fu-Zhu-Yu Capsule for Patients with Qi Stagnation and Blood Stasis Pattern: A Nested Case-Control Study. (18th November 2019) - Chen, Guang; He, Haoqiang; Hu, Kun; Gao, Jialiang; Li, Jun; Han, Mei; Wang, Jie
Abstract : Objectives . To identify the sensitive biomarker to predict the effectiveness of Xue-Fu-Zhu-Yu capsules (XFZYC). Methods . This nested case-control study included 5 patients with response to XFZYC in the treatment group, 5 patients with no response to XFZYC also in the treatment group, and 5 patients in the control group treated with placebo who participated in the previous RCT. The mRNAs, miRNAs, lncRNAs, and circRNAs were sequenced by next-generation sequencing and differential-expressed (DE) RNAs were identified if p value ≤ 0.05 and fold change ≥2, bioinformatics analysis was conducted in terms of function annotations and signaling pathways, and then sensitive biomarker was analyzed based on real-time PCR. Results . The distributions of clinical characteristics between the selected participants from treatment group and placebo group were well balanced. A total of 1156 DE RNAs, 388 miRNAs, 1954 lncRNAs, and 560 circRNAs were identified, which was associated the mechanism of XFZYC and composed the targeted potential biomarkers for further real-time PCR. The DE RNAs were enriched in KEGG pathways pertaining to pathogenesis of Qi Stagnation and Blood Stasis- (QS & BS-) & associated diseases such as coronary heart disease and digestive diseases. The expression level of FZD8 was significantly higher in response patients than that in nonresponse patients (p = 0.041 ) and circRNA_13799 significantly lower in response patients than that in nonresponse patients (p = 0.040 ) based on real-time PCR. Patients with higher expression level of FZD8 with 75% stratification have significantly higher reduction in the questionnaire score (p = 0.010 ), and the area under the curve (AUC) was 0.765 (95%CI = 0.593–0.936; p = 0.014 ). Conclusions . FZD8 might perform the sensitive biomarker for predicting the effectiveness of XFZYC. However, further prospective cohort study was warranted to confirm the exact specificity and sensitivity of this biomarker.